The „Bridge Effect” - Mayer, G; Mayer, S; Waitz, R (Thrombosis and Haemostasis, 1960)
The “Bridge effect“ consists in the fact that an incomplete thromboplastin, tested by the thromboplastin generation test of Biggs and Douglas on a substrate having a deficiency in its own thromboplastin generation, coagulates it more slowly than a normal substrate. It is observed when the factorial deficiencies of the substrate and the thromboplastin correspond with each other (hemophilic — hemophilic, Christmas — Christmas), it is weak and inconstant (Christmas thromboplastin — hemophilic substrate) or non existent (hemophilic thromboplastin — Christmas substrate) when they are crossed. It is eliminated by an adequate correction of the substrate (AHG added to the hemophilic substrate, PTC added to the Christmas substrate). The “Bridge effect“ is a source of error which must be taken into account in the manipulation of thromboplastin generation tests.